An Adjuvanted Inactivated SARS-CoV-2 Microparticulate Vaccine Delivered Using Microneedles Induces a Robust Immune Response in Vaccinated Mice - Sharon Vijayanand; Smital Patil; Ipshita Menon; Keegan Braz Gomes; Akanksha Kale; Priyal Bagwe; Mohammad N. Uddin; Susu M. Zughaier; Martin J. D’Souza (Pharmaceutics, 2023)
SARS-CoV-2, the causal agent of COVID-19, is a contagious respiratory virus that frequently mutates, giving rise to variant strains and leading to reduced vaccine efficacy against the variants. Frequent vaccination against the emerging variants may be necessary; thus, an efficient vaccination system is needed. A microneedle (MN) vaccine delivery system is non-invasive, patient-friendly, and can be self-administered. Here, we tested the immune response produced by an adjuvanted inactivated SARS-CoV-2 microparticulate vaccine administered via the transdermal route using a dissolving MN. The inactivated SARS-CoV-2 vaccine antigen and adjuvants (Alhydrogel® and AddaVax™) were encapsulated in poly(lactic-co-glycolic acid) (PLGA) polymer matrices. The resulting MP were approximately 910 nm in size, with a high percentage yield and percent encapsulation efficiency of 90.4%. In vitro, the vaccine MP was non-cytotoxic and increased the immunostimulatory activity measured as nitric oxide release from dendritic cells. The adjuvant MP potentiated the immune response of the vaccine MP in vitro. In vivo, the adjuvanted SARS-CoV-2 MP vaccine induced high levels of IgM, IgG, IgA, IgG1, and IgG2a antibodies and CD4+ and CD8+ T-cell responses in immunized mice. In conclusion, the adjuvanted inactivated SARS-CoV-2 MP vaccine delivered using MN induced a robust immune response in vaccinated mice.